Management of Geodetic and Cartographic Processes: Evidence from 12 Cities in the Union of Polish Metropolises - Magdalena INGLOT (Communications of International Proceedings, 2024)
The aim of the article is to identify practices in the field of geodetic and cartographic tasks provided by the largest cities in Poland, in terms of the scope of execution and the scale of expenditure. The research was conducted using the desk research method, and the data source was 12 budget reports from all cities belonging to the Union of Polish Metropolises for the year 2023, with particular emphasis on the task budget section. The article presents the scale of expenditures related to salaries, statutory tasks and investment activities. It also outlines the scope of work performed by individual cities, which allows the identification of current trends and an assessment of efficiency. The research results indicate that the structure of task presentation by individual cities is not tied to any systematic classification and is not presented uniformly, which affects its comparability. Nevertheless, verification of data on geodetic and cartographic processes can contribute to benchmarking analyses and the identification of good practices, and in the long term, to setting appropriate goals for optimizing expenditures and preventing legal and spatial conflicts.
Keywords: geodetic processes; cartographic processes; task management; public expenditures; benchmarking; city management